Identification of molecular markers for pre-thrombotic state: validation in the rabbits with tibia fracture or lung cancer - Qi, Yan; Hu, Xin; Chen, Jing; Wu, Qian; Ying, Xiaobin; Shi, Yan (Translational Cancer Research, 2019)
Background: Currently there is no reports on identifying molecular markers for pre-thrombotic state in animal experimental settings. It’s necessary to explore the potential molecular markers for pre-thrombotic state to provide evidence for the pharmacotherapy of venous thromboembolism (VTE). Methods: A total of 36 male rabbits were randomly divided into Sham, Tibia fracture, Lung cancer, Tibia fracture and lung cancer group. Pro-thrombin time (PT), thrombin time (TT), activated partial pro-thrombin time (APTT), fibrinogen (FIB), D-dimer (D-D) and anti-thrombin III (AT-III) at baseline, 1, 7, 14 and 21 days after operation were detected. Immuno-histochemical staining of tumor tissue sections was performed to observe the expression of CD31, VEGF and vWF. Western blot and qPCR were used to detect the expression levels of ANG and VEGF gene in tumor tissues. Furthermore, we analyzed the tumor tissue with HE staining, immunochemistry, qPCR and Western blot. all the data were statistically analyzed with GraphPad Prism 6. Results: There were 0, 1, 2, 4 cases of VTE in sham, tibia fracture, lung cancer, tibia fracture and lung cancer group respectively. The level of PT, APTT, TT and AT-III were significantly decreased after operation (all P